Speech acts in the Manbijiat maqama of Ibn Al-Wardi - حيدر, علي; الرَّاهب, سميرة; العلي, منى (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
Pragmatic focused on the study of verbal methods and Semantic effects associated with the Maqama context, pragmatic interest in language is manifested by Focusing on the method of use , linking it to the achievement plan , and its impact on the listener . The research attempts to high light the most important verbal acts used by Ibn Al-Wardi in his maqama. In which he was able to influence the recipient , by specifying the achievement purposes of the various direct and indirect verbal acts . The research found that maqama discourse is a fertile field for practicing pragmatic procedures represented in the theory od verbs acts thonks to its linguistic issues and contextual dimensions .